2012
DOI: 10.1016/j.compedu.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

How to improve the peer review method: Free-selection vs assigned-pair protocol evaluated in a computer networking course

Abstract: This study provides field research evidence on the efficiency of a "free-selection" peer review assignment protocol as compared to the typically implemented "assignedpair" protocol. The study employed 54 sophomore students who were randomly assigned into three groups: Assigned-Pair (AP) (the teacher assigns student works for review to student pairs), Free-Selection (FS) (students are allowed to freely explore and select peer work for review), and No Review (NR) (control group). AP and FS student groups studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…The First study [14] compared the effectiveness of the Free-Selection protocol against the typical Assigned-Pair one, where students work in instructor-defined dyads (playing both the roles of author-reviewer). Results showed that students in the FS group performed significantly better than those in the AP group in acquisition of domain knowledge (p<0.05).…”
Section: Introductionmentioning
confidence: 99%
“…The First study [14] compared the effectiveness of the Free-Selection protocol against the typical Assigned-Pair one, where students work in instructor-defined dyads (playing both the roles of author-reviewer). Results showed that students in the FS group performed significantly better than those in the AP group in acquisition of domain knowledge (p<0.05).…”
Section: Introductionmentioning
confidence: 99%
“…Peer reviews are also often biased towards a higher score in comparison to expert reviews (Papadopoulos et al 2012), (Lu et al 2015), which might distort a student's perspective on the quality of their work.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, within earlier studies, perception of the task was the main theme found within this field of inquiry (1) but the overall examination of influence and perceived growth of the participants, who conducted the review, was under-investigated. Furthermore, very few investigations (a) define peer review in comparison to peer assessment (16) , (b) examine the peer review process from the vantage of the feedback provider (1) , sometimes referred to in the literature simply as the reviewer, nor (c) examine the use of peer review when using an auto-assign feature found within a more current LMS, such as Canvas, in comparison to externally or proprietary-created tools for peer review management.…”
Section: The Power Of Peer Review…but Only For Writing Assessmentmentioning
confidence: 99%
“…Many researchers have even examined peer review in support of learning in all different conditions, such as: (a) conducted in synchronous (13) or asynchronous formats (14)(15) (b) selecting to use pair-wise reviewer assignment in lieu of free selection processes (16) , (c) utilizing pre-made software programs for the management of the overall peer review process (12) , or (d) for the purpose of using an institutional peer review program to manage first-year student assessment expectations (17) . Additionally, Sondergaard & Mulder (1) (2012) provide a substantial list of advantages for using peer review to establish a deeper learning atmosphere supported by timely feedback and the creation of "an alternative channel for student engagement and participation," (p. 347).…”
Section: The Power Of Peer Review…but Only For Writing Assessmentmentioning
confidence: 99%